Nitric Oxide in β-Thalassemia - Sriwantana, Thanaporn; Srihirun, Sirada; Sibmooh, Nathawut (Journal of Basic and Applied Pharmacology, 2019)
Nitric oxide (NO) has multiple physiologic functions and its decrease or increase is associated with pathophysiology of diseases. NO is produced by nitric oxide synthase (NOS)-dependent and NOS-independent pathways. The NO concentrations and rate of production from different pathways are determinants of its biological functions. NO at low levels produced by constitutive NOS maintains adequate blood flow and inhibits platelets in normal situation, while NO at high levels produced by inducible NOS plays role in pathophysiologic process. In NOS-independent pathway, NO is produced from nitrite by the nitrite reductase activity of deoxyhemoglobin. In thalassemia, iron overload and oxidative stress lead to endothelial dysfunction and decreased NO, which are associated with platelet hyperactivity and pulmonary hypertension. Here, the preclinical and clinical studies of NO-related and nitrite therapy in β-thalassemia are reviewed.